Neural compass in the sky - Zhou, Yue-Qing; Knierim, James J (Science (American Association for the Advancement of Science), 2025)
Head-direction neurons maintain stable directional signals during large-scale navigation in the wild.Head-direction neurons maintain stable directional signals during large-scale navigation in the wild.